Sejarah Perjalanan Haji Orang Melayu Ke Makkah (1911-2017 Masihi): The History of Pilgrimage Travel to Mecca among Malays (1911-2017) - Wan Mahmud, Wan Zahari; Abdul Hamid, Ahmad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2020)
Performing pilgrimage in the Holy Land of Mecca is such a meaningful for the Malay-Muslims. They have recorded some great history of pilgrimage travel since they had to undergo many challenges before successfully completing the fifth pillar of Islam. Therefore, the purpose of this article is to scrutinize the history of pilgrimage travel among Malays which have been recorded around the year 1911-2017 Century and their requirements before they departed to Mecca. Analysis was carried out based on the data library through historical method. Finding shows that there were many Malays who went for pilgrimage around the year 1911-2017 Century by ships and airplanes. They also have provided many requirements before departing to Mecca.